Process Development and Optimization of Carbon-Based Thin Film Deposition through Ablation of Graphite - Low, Andrew Chun Wey; Damideh, Vahid*; Saw, S. H.; Lim, Chin Seong* (Trans Tech Publications, 2016)
This paper reports the deposition of carbon nanomaterials on silicon substrate using a dense plasma focus device. The film property is studied using a field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX). The first test was deposited using 1, 3, 5, and 7 focus shots while the second test was carried out using 1 focus shot at 2, 3, 4, 5 and 7 Torr. Both tests were conducted with neon as filling gas at 7 Torr at distance of 8cm from the anode tip. In the first test, FESEM images exhibit a non-homogenous, non-uniformed and largely agglomerated carbon deposition at all films as pressure of filling gas increases. The EDX mapping confirms that carbon content in substrate increases from 10% to 30% as number of shot increases, and there is more carbon content detected in the centre position than the off-centre position. There is also a decrease in carbon content 35% to 25% as pressure of gas increases.